FUNCTIONAL EFFECTS OF AQUATIC EXERCISE IN PREGNANT: A SYSTEMATIC REVIEW - Cordeiro, André Luiz; Santos, Bianca Oliveira; Souza, Camilla Macêdo; Santos, Rebeka Gonçalves (Clinical and Biomedical Research, 2021)
Introduction: During pregnancy, all systems of the human body change, together with anatomical changes. It is common for women to decrease the intensity of physical activities, especially in the last trimester. Water activities during pregnancy have shown positive effects for this population. Objective: To review the effects of functional exercises in the aquatic environment for women during pregnancy. Methods: Systematic review using the PICO methodology, researched on the Pubmed, SciELO, LILACS and Science Direct platform, using the keywords: Pregnancy, hydrotherapy, quality of life, pregnant women, aquatic environment. Published randomized controlled trials that addressed the functional effects of aquatic exercise in pregnant women, published in English, Spanish and Portuguese in the years 2010 to 2020 were included. In addition, the Boolean operators "and" and "or" were used. The research was carried out from May to July 2020. Results: The search initially resulted in 537 articles, of which 95 records remained after duplicates were removed, with 14 articles remaining. At the end, 5 articles were included. The samples ranged from 46 to 140 participants. Of the five selected studies, all obtained positive results, the reduction of pain during pregnancy, the view of this favoring weight control, blood pressure and improvement in sleep quality. Conclusion: It is concluded that aquatic exercise for pregnant women acts positively in weight control, improves sleep quality, controls blood pressure, decreases low back and joint pain.